Haitianos em Cuiabá : um estudo sobre interferências do crioulo haitiano na aprendizagem do português escrito - Matos, Ana Cecília Fonseca (2020)
This dissertation proposes to present the results of research into linguistic interference between Haitian Creole and Portuguese written by Haitians in Cuiabá-MT. The study was carried out during the classes of Portuguese as an Additional Language at UFMT, which served the public of Haitians, both from the external community and the internal community of the university. Classes were held twice a week for two hours each. The total number of subjects investigated was ten Haitians. The aim of the study was to analyze and understand the interference between Haitian Creole and written Portuguese as an additional language. To meet this objective, the path taken was the identification of interference phenomena; the analysis of the written productions of the target audience; and the classification of the interferences that emerged. As research instruments, several writing activities were carried out in the classroom, which served for further analysis. The research sought to contextualize Haitian Creole and Haitian society from its colonization to the present day, as well as contextualizing the formation of Brazilian Portuguese. The theoretical construct of the research ran through the conceptions of language acquisition, understanding of the concept of interlanguage and contrastive analysis of errors, reaching the theory of linguistic interference. The methodology, of a qualitative character, made an overview of new approaches in research in applied linguistics and took a look at the phenomena that emerged to classify them as lexical and morphosyntactic. Among the results, it was possible to notice that some grammatical aspects suffer more interference from Haitian Creole in learning Portuguese than others, such as verbal inflection and gender marking. In conclusion, this study directly contributes to teaching-learning practices in terms of understanding and contributing to the contrastive analysis of errors in the learning of Brazilian Portuguese by Haitians, in an immersion situation.